UTILIZATION OF EMPTY SPACE UNDER FLY OVER AS AN OPEN PUBLIC SPACE - Rona Fika Jamila; Retno Wijayaningsih (MODUL, 2022)
The development of transportation facilities is also important to accommodate the mobility of city residents both by private vehicles and by public transportation. One way to break up the transportation complications is to build an overpass or commonly known as a fly over, and this effort is usually quite successful. However, there is another side that often escapes the government's fly over planning, namely the creation of new spaces under the overpass that are not clearly utilized, so that spontaneously, the spaces that are formed are used "at will" by the community. The purpose of this study is to obtain a variety of shapes and dimensions, as well as where the location of residual space under the fly over, Obtaining community use of residual space under the fly over, Obtaining community behavior in utilizing the residual space under the fly overThis research is a basic research that has a Level of Technology 1 and has a target output in the form of national accredited national journals.